2016
DOI: 10.1111/mec.13691
|View full text |Cite
|
Sign up to set email alerts
|

Applying landscape genetics to the microbial world

Abstract: Landscape genetics, which explicitly quantifies landscape effects on gene flow and adaptation, has largely focused on macroorganisms, with little attention given to microorganisms. This is despite overwhelming evidence that microorganisms exhibit spatial genetic structuring in relation to environmental variables. The increasing accessibility of genomic data has opened up the opportunity for landscape genetics to embrace the world of microorganisms, which may be thought of as 'the invisible regulators' of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…The divergence in finch gut microbiome communities we observe across islands highlights the role of dispersal limitation in determining microbial community structure within wild host species (reviewed in [16]). Previous work has shown that geographic distance increased the distance between gut microbiomes in mammalian species, tested in 17 species across the Americas [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The divergence in finch gut microbiome communities we observe across islands highlights the role of dispersal limitation in determining microbial community structure within wild host species (reviewed in [16]). Previous work has shown that geographic distance increased the distance between gut microbiomes in mammalian species, tested in 17 species across the Americas [15].…”
Section: Discussionmentioning
confidence: 99%
“…The geographic distance provided additional explanatory power compared to the sole interpretation based on phylogenetic distance. Notably, environmental drivers of microbial community composition are increasingly being found with the emergence of novel genomic and spatial analyses [16].…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneous space or 'landscape' affects microevolutionary dynamics at various scales, leaving genomic signatures that may be identified (Biek and Real, 2010). To date, in this emerging field, Dudaniec and Tesson (2016) noted that little attention has been paid to the linkage between microorganism dispersal and environmental factors, despite evidence of non-random distributions and patterns of isolation by distance (IBD) within populations (Martiny et al, 2006). Because of their high dispersal abilities (Taylor et al, 2006), microbes were long thought to display little genetic biogeographic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“… 10 For example, it is often expected that vertically transmitted microorganisms are more likely to have beneficial effects on their hosts than horizontally transmitted ones. 11 , 12 Studying how insects acquire microbial symbionts will therefore better our understanding of the spatiotemporal dynamics of microorganisms among hosts and resource patches 13 and our understanding of the evolution of symbiotic associations. 4 …”
Section: Introductionmentioning
confidence: 99%